Biological Control of Wood Destroying Organism Using Plant Extracts Collected from Mt. Merapi National Park, Indonesia - Maya Ismayati; Deni Zulfiana; Didi Tarmadi; Anis Sri Lestari; Ni Putu Ratna Ayu Krishanti; Setiawan Khoirul Himmi; Anugerah Fajar; Sulaeman Yusuf (Biosaintifika: Journal of Biology & Biology Education, 2019)
Due to the climate change and global warming, the biodiversity database has gained the attention of the government. In line with the Indonesian Biodiversity Strategy and Action Plan (IBSAP), we have collected plants with insecticidal activity based on the local wisdom. This program aimed to protect Indonesian biodiversity from deforestation along with the loss of the number of species. This research’s goal was to evaluate termiticidal and antifungal properties from some plant extracts collected from the Turgo forest area, Mt. Merapi National park, Java. Three potential plants were evaluated. Based on specimen identification, the three plant samples were Kina (Cinchona sp.), Kamadoh (Dendrocnide stimulans (L.f.) Chew), and Keremi (Homalanthus populneus (Geiseler) Pax). The phytochemical test showed that Kina contained alkoloid, falvonoid, saponin, and tannin, whereas Kamadoh and Keremi contained saponin and tanin, respectively. Overall, all plant extracts have the termiticidal activities and able to inhibit wood- decay fungi with the inhibition percentage around 60% - 100%. Leaf extracts of Kina (Cinchona sp) and Keremi (Homalanthus populneus (Geiseler) showed the highest activity as wood-decay fungi inhibitor. The disclosure of the potential of bioinsecticides from some plants originating from Mount Merapi is very important before being lost due to deforestation and the Mount Merapi disaster. Thus, the potential bioinsecticide in these plants can increase its economic value as a substitute for synthetic insecticides that are friendly to the environment.